Parent birds and their young - Skutch, Alexander F. (Alexander Frank), 1904-2004. (Austin : University of Texas Press, 1976)
"A detailed survey ... of the family life and reproductive behavior of birds, from the formation of pairs to the young birds' attainment of independence."
Includes index.
Bibliography: p. [463]-483.
Keywords: Birds -- Behavior; Parental behavior in animals; Birds; Animal behavior; Parental behavior in animals